Unwinding of the uniform lying helix structure in cholesteric liquid crystals next to a spatially uniform aligning surface - Salter, P; Carbone, G; Jewell, SA; Elston, S; Raynes, P (2009)
The symmetry of the cholesteric uniform lying helix (ULH) structure, where the helix axis is aligned in a single direction parallel to the device substrates, is not compatible with a uniform surface alignment and an unwinding of the helical structure is expected at the interface. Fluorescence confocal polarizing microscopy experiments are performed on the interface between a bulk ULH and a uniform aligning surface (for both planar and homeotropic alignments). The results are analyzed in the framework of a finite difference numerical simulation based on the Frank elastic distortion, to determine relevant director structures. An optical model is introduced to predict three-dimensional fluorescence profiles for the structures. Comparison of experimental and theoretical results shows that the equilibrium structure of the system involves a continuous unwinding of the helix close to the surface. © 2009 The American Physical Society.